ANALISIS KORELASI USIA PESAWAT AIRBUS A320-200 TERHADAP JUMLAH KOROSI YANG TIMBUL MENGGUNAKAN METODE KORELASI PEARSON PRODUCT MOMENT - Reynaldo Mulya Tedja; Mufti Arifin; Erna Shevilia Agustian (FTK UNSURYA, 2023)
Corrosion is the destruction of materials caused by the environment, where metals separate from their metal atoms and form compounds from water or gas, resulting in oxidation until the metal atoms disappear. Corrosion can also be referred to as material that is damaged by the environment and is mostly caused by natural impacts that increase as the age of the aircraft increases. Failure to maintain the strength of the main structure is caused by excessive stress that occurs in the corrosion area resulting in cracks in the structure. Due to the frequent occurrence of corrosion in the aircraft, observations, data analysis and further literature studies were carried out. This study aims to determine the relationship between aircraft aging and the amount of corrosion found during periodic